HIV/AIDS EPIDEMICS AND HUMAN DEVELOPMENT AT THE BEGINNING OF THE 21ST CENTURY: CASE STUDIES OF UGANDA AND ESTONIA - Preis, J.; Kopp, J. (Інфекційні хвороби, 2013)
This paper analyzes how the HIV pandemic has influenced levels of development throughout the world, quantitatively expressed by the Human Development Index (HDI). Regional examples in Uganda and Estonia are used to describe and explain the results of this investigation. The change in world HDI distribution from 2000 to 2005 was analyzed and the patterns found were compared to that of the HIV/AIDS epidemics between 2001 and 2005. The regional examples are the result of detailed monitoring during prevention and care work in the aforementioned countries through the Geography Department of the University of Western Bohemia in cooperation with NGOs ACET Czech Republic and ACET International. HDI progression from 2000 to 2005 did not cause significant discrepancies in HDI levels between different countries, but it was confirmed that HIV/AIDS can hinder the human development measured by HDI. In Sub-Saharan Africa, the HIV/AIDS epidemic slightly decreases, but this is only partially projected into the growth of HDI (classic positive example is Uganda). The second most afflicted region by HIV/AIDS in terms of relative numbers is Central/Eastern Europe and central Asia. In this region both HIV prevalence and HDI grew between 2000 and 2005. The epidemic, however, is not yet a factor that would significantly hinder the HDI growth on national levels.